In situ cyclic telescoping of multi-walled carbon nanotubes in a transmission electron microscope. (October 2016) - Moore, Katherine Elizabeth; Cretu, Ovidiu; Mitome, Masanori; Golberg, Dmitri
Abstract: In this work, we study the cyclic telescoping of multi-walled carbon nanotubes (MWCNTs) inside a high-resolution transmission electron microscope. The nanotubes are observed in real time, while simultaneously measuring their electrical properties. Experiments are conducted by first 'sharpening' a MWCNT by approaching it with a piezo-controlled tungsten tip and applying a single voltage pulse. This results in controlled and localized peeling of the outer walls, giving rise to a telescope structure. The exposed core is then contacted with the tungsten tip and reproducibly pulled out then re-inserted, while measuring conductance behaviour at each movement step. Results demonstrate that an electrical current can be maintained for multiple in-and-out cycles, and for telescoping distances of up to 650 nm. The systems display complex conductance behaviour, with most MWCNT telescopes demonstrating diminishing conduction (and current) as a function of the number of cycles, while for some these properties improve. Control experiments have been carried out to investigate the effect of current annealing and beam damage on whole MWCNTs. One potential application for these structures is use as flexible electrical contacts, which allow for relative motion of the two electrodes, while maintaining electrical conduction.